2019
DOI: 10.1088/1361-6560/aaf58d
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive vascular occlusion with HIFU for venous insufficiency treatment: preclinical feasibility experience in rabbits

Abstract: Venous insufficiency is a common disease arising when veins of the lower limb become incompetent. A conventional surgical strategy consists in stripping the incompetent veins. However, this treatment option is invasive and carries complication risks. In the present study, we propose noninvasive high-intensity focused ultrasound (HIFU) to treat lower limbs venous insufficiency, in particular incompetent perforating veins (mean diameter between 2-6 mm). Sonication parameters were designed by numerical simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Experimental studies have also searched for ways to focus the damage to specific vessels by echo contrast and beam control, but the results are still initial 12 . One experimental study in rabbits showed that the HIFU can close by thermal ablation veins as large as 6 mm with 15 days of follow up 13 . Obermayer has recently shown that HIFU can cause thermal ablation of varicose veins, perforators and great saphenous veins.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have also searched for ways to focus the damage to specific vessels by echo contrast and beam control, but the results are still initial 12 . One experimental study in rabbits showed that the HIFU can close by thermal ablation veins as large as 6 mm with 15 days of follow up 13 . Obermayer has recently shown that HIFU can cause thermal ablation of varicose veins, perforators and great saphenous veins.…”
Section: Discussionmentioning
confidence: 99%
“…Each vein was treated with a sequence of HIFU sonications distributed in a row of multiple spots along the vein with a 3.5 mm spacing. Continuous HIFU sonications were applied for 8 s with a mean acoustic power of 84 ± 6 W, according to the power used in a preliminary study performed on rabbit saphenous veins [22]. The corresponding spatial-peak intensity estimated from linear extrapolation from low power hydrophone measurement in water is 28 kW.cm À2 .…”
Section: Clinical Signs Evaluatedmentioning
confidence: 99%
“…The use of HIFU as a noninvasive alternative to endovenous treatments of varicose veins has already been investigated in a number of preclinical studies [17][18][19][20][21][22] and the ability to occlude small veins in vivo noninvasively with thermal HIFU has been demonstrated [18,22]. However, the efficacy and safety of the ablative procedures were demonstrated in the short term only, at most two weeks after treatments [22]. One study conducted by Delon-Martin et al [18] examined HIFU-mediated vascular occlusion with a longer follow-up and reported that a vein was successfully occluded 2 days post-HIFU but recanalized 28 days after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Skin, fat and muscle tissue could not be segmented on the CT scans. Soft tissues were thus modeled as homogeneous tissues as was done in [36]. Table 1 summarizes the acoustical properties of the tissues and gel that were used in the simulation.…”
Section: Acoustic Modelingmentioning
confidence: 99%